Evaluasi Fisik dan Kimia Dedak Padi pada Berbagai Level Penambahan Sekam: Physical and Chemical Evaluation of Rice Bran with Various Level of Husk Addition - Eneh Maesaroh; Rima Shidqiyya Hidayati Martin; Anuraga Jayanegara; Tri Aminingsih; Nahrowi Nahrowi (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
The aim of this research was to analyze the physical and chemical properties of rice bran with husk addition. The percentage of husk addition was 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100%. Husks were grounded and mixed with rice bran homogeneously. The mixture was analyzed for physical properties, proximate analysis and van Soest analysis. The variables in this study included visualization of husk addition in rice bran, specific gravity (SG), bulk density (BD), moisture content (MC), ash, crude protein (CP), ether extract (EE), crude fiber (CF), acid detergent fiber (ADF), cellulose and lignin. Data were presented descriptively and the correlation between each variable was conducted. The results showed that there were differences in visualization in each level of husk addition in rice bran. The addition of husks in rice bran increased the ash (Δ = 11.89), CF (Δ = 22.75), ADF (Δ = 47.23), cellulose (Δ = 24.04) and lignin (Δ = 7, 40). The decrease in SG, BD, MC, CP and EE in mixing rice bran and husk were Δ = 0.62; 62.85; 3.64; 5.73 and 9.21 respectively. The correlation between the physical properties and the chemical properties showed significant correlation (p<0.01). The addition of husks to rice bran affected the physical and chemical qualities. Key words: chemical evaluation, husk, physical evaluation, rice bran